Social and solidarity economy in higher education: a space for innovation (Volume 3) (2020)
The third and last volume of the collection Social and Solidarity Economy in Higher Education: A Space for Innovation presents curricular experiences in universities in Colombia, Brazil, Argentina, Portugal, and Spain. It begins with the systematization of an experience that emerged in the late 1970s in Colombia, which has inspired the creation of subsequent formal and non-formal programs to strengthen the theory and practice of solidarity economy in the territories. Then, the training activities of the SSE in the classroom were linked to mathematics and its contributions to the popular economy. In the line of curriculum development, its two chapters show the innovative contribution of the teaching of the social economy in a master’s degree in Portugal and of the production of knowledge through undergraduate projects and projects in Colombian universities. The following chapters explore the aesthetic experiences in the solidarity economy, as well as the role that virtual education plays in the development of entrepreneurial skills. Finally, Brazil once again provides an example of the capacity of universities for solidarity entrepreneurship and innovation (the LabEcosol experience and its impacts on the territory).